A mechanism study of synthesis of Li4Ti5O 12 from TiO2 anatase - Yuan, T.; Cai, R.; Ran, R.; Zhou, Y.; Shao, Zongping (Elsevier B.V., 2010)
The formation mechanism of a spinel-type lithium titanate Li 4Ti5O12 with TiO2 anatase as raw material, in both a conventional solid-state reaction (SSR) and a cellulose-assisted glycine-nitrate combustion (cellulose-GN) process are comparatively studied. XRD characterization demonstrates high-purity Li 4Ti5O12 forms at 750 °C by the cellulose-GN synthesis, which occurs at a temperature at least 100 °C lower than that via SSR. The solid-phase reaction between TiO2 and lithium compounds to form Li-Ti-O spinel and the phase transition of TiO2 from anatase to "inert" rutile phase occur competitively during both synthesis processes. SEM results suggest that the solid precursor from the cellulose-GN process has a smaller particle size and a more homogenous mixing of the reactants than that in the SSR. Temperature-programmed oxidation experiments demonstrate that cellulose thermal pyrolysis creates a reducing atmosphere, which may facilitate the oxygen-ion diffusion. Both factors facilitate the formation of Li-Ti-O spinel, while the TiO2 anatase transforms to TiO2 rutile during the SSR, which has slow lithium-insertion kinetics. As a result, a high calcination temperature is necessary to obtain a phase-pure Li4Ti5O12. Charge-discharge and EIS tests demonstrate the Li4Ti5O12 obtained by the cellulose-GN process shows much better low-temperature electrochemical performance than that obtained by standard SSR. This improvement attributes to the reduced particle size due to the lower synthesis temperature. © 2010 Elsevier B.V. All rights reserved.